ANTIOXIDANT CAPACITY, MINERAL CONTENT AND ESSENTIAL OIL COMPOSITION FROM SELECT ALGERIAN MEDICINAL PLANTS - Hadjira Guenane1; Abdelaziz Gherib; Boulanouar Bakchiche; Ángel A. Carbonell-Barrachina; Francisca Hernández; Marina Cano-Lamadrid (Scientific Study & Research: Chemistry & Chemical Engineering, Biotechnology, Food Industry, 2017)
The objective of the present study was to analyze the total antioxidant capacity, minerals contents of four plants (Juniperus oxycedrus, Thymus capitatus, Laurus nobilis and Eruca vesicaria) and chemical composition of the essential oils of the aerial parts of T. capitatus. Their antioxidant activity was assessed by DPPH, ABTS and FRAPS assays. Total phenol and flavonoid contents of the extracts were also determined. The results showed that the L. nobilis extract had the highest total phenolic and flavonoids contents (19.11 ± 0.22 mg GAE•g-1 dw, 4.47 ± 0.12 mg QE•g-1 dw, respectively). The extract of E. vesicaria had the highest value of TEAC for scavenging DPPH, whereas L. nobilis extract was active for ABTS and FRAP. GC/MS analysis revealed that the essential oil from the aerial parts of T. capitatus contained thirty-seven compounds; thymol was the major constituent (82.79 %). Atomic absorption spectroscopy showed high levels of Ca, K, Mg and Fe, and trace amounts of Zn, Cu and Mn in all four extracts.